DIPLOMASI PUBLIK DAN POLITIK GENDER DI GLOBAL SELATAN: MENGGUGAT NETRALITAS REPRESENTASI DI INDONESIA, AFRIKA SELATAN, DAN BRASIL - Roy Setiawan; I Kadek Andre Nuaba (Mandala: Jurnal Ilmu Hubungan Internasional, 2025)
Public diplomacy is often understood as a strategic communication practice that is neutral and universal. However, in the context of Global South countries, this presumed neutrality deserves to be challenged, as it tends to overlook the gendered dimensions embedded in the construction of national image and international legitimacy. This study examines how Indonesia, South Africa, and Brazil represent gender within their public diplomacy strategies, and how these practices reflect or contest global power relations. Employing feminist constructivism and postcolonial feminism as analytical frameworks, the research analyzes policy documents, digital campaigns, and official media narratives. The novelty of this study lies in its integration of gender analysis and epistemic justice within the field of public diplomacy in Global South contexts—an area often marginalized in mainstream international relations literature. The research not only reveals the symbolic and depoliticized representations of gender in public diplomacy, but also highlights resistant practices by non-state actors who reimagine diplomacy in more inclusive terms. It argues that gender-based public diplomacy is not merely about image-making, but about a state's willingness to confront its own social complexities and build legitimacy through more just and reflective narratives.